Hahlo's casebook on Company law - Hahlo, H. R.; Trebilcock, M. J. (London : Sweet and Maxwell, 1977)
This is an introductory text in company law. Ii examines: elements and history of partnership law; foundation of company law; the constitution of a company; capital structure; dividends and profits; company general meeting; duties and liability of directors; accounts, accountants and auditors.
Distributed in Canada and the U.S. by Carswell Co., Agincourt, Ont.
Includes bibliographical references and index.
lje 24/01/2019
Loans
Keywords: Corporation law; Company law; United Kingdom